Perancangan Sistem Informasi Manajemen Pelatihan Kursus Berbasis Web Pada CV Nixtrain Infotama - Khamdun Khamdun; Esron Rikardo Nainggolan; Jordy Lasmana Putra (JURNAL ILMIAH INFORMATIKA, 2022)
Training activities are usually carried out face-to-face, but along with the development of increasingly advanced times, especially in the field of technology, business actors, especially in the field of training, find more efficient and effective ways to run their business or business. The design of a website-based training management information system will make it easier for prospective trainees to access updated training information anywhere and anytime using the internet. Then it will reduce damage and loss of data because data about training activities is stored safely and neatly on a website. The design of this website itself is designed by the methodology used is Object Oriented Programming or commonly abbreviated as OPP.